DEVELOPMENT OF INDIVIDUAL SWIMMING PROGRAMS FOR STUDENTS TAKING INTO ACCOUNT THEIR PHYSICAL FITNESS AND HEALTH CHARACTERISTICS - Ruzieva Mahliyo Kayumovna (Proximus Journal Publishing, 2024)
In the conditions of the modern rhythm of life, students often experience a deficit of physical activity. Swimming, being one of the most accessible and effective sports, helps to strengthen health, increase physical endurance and improve the psycho-emotional state. However , standard swimming programs do not always take into account the individual characteristics of each student, which can reduce their effectiveness and even lead to injuries. Therefore, the development of individual swimming programs taking into account the physical fitness and health characteristics of students becomes an urgent task.
Keywords: account; effectiveness; programs